Parental Involvement in Early Childhood Education: A Bibliometric Analysis in the Era of the Independent Curriculum - Nurfadilah, Lira Rizqi; Hasanah, Nor; Febriyani, Febriyani; Khoirunnisa, Diana; Hartanti, Rayani Dinar; Yuniar, Dias Putri (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: The Independent Curriculum (Kurikulum Merdeka), which has been widely implemented in Indonesia since 2021, emphasizes flexibility, student-centered learning, and contextualized teaching. In early childhood education (ECD), the role of parents is crucial in supporting holistic development and the successful implementation of this curriculum. However, research focusing specifically on the extent and nature of parental involvement in ECD within the framework of the Independent Curriculum remains limited and fragmented. Aims and scope of paper: This paper aims to review and analyze existing studies on parental involvement in early childhood education in the context of the Independent Curriculum era. The focus is on how collaboration between parents, teachers, and schools contributes to enhancing children's learning experiences and developmental outcomes. By conducting a bibliometric analysis, this review also seeks to map the current state of research and identify gaps for future studies. Methods: This study uses a systematic review method with a bibliometric approach. Secondary data were collected from two major academic databases: Google Scholar and Scopus. The publication timeframe analyzed spans from 2020 to 2024 to capture recent developments related to the implementation of the Independent Curriculum. Articles were selected based on their relevance to parental involvement and early childhood education. Results: The analysis identified 11 relevant journal articles that highlight the significant role of parents in supporting early childhood education during the Independent Curriculum era. These studies consistently emphasize the importance of active parental collaboration with teachers and schools. Such collaboration has been shown to improve children's engagement, emotional well-being, and academic readiness, thereby reinforcing the goals of the curriculum. Contribution: This review contributes to the growing body of literature by offering a synthesized overview of how parental involvement is addressed in the context of Indonesia's Independent Curriculum. It provides insights for educators, policymakers, and researchers on the importance of fostering strong partnerships between families and educational institutions. Moreover, the findings serve as a foundation for future research that can explore effective strategies and intervention models to strengthen parental engagement in early education.